Earthworm species in native and planted forests in Brazil - Demetrio, Wilian Carlo; Da Fonseca, Priscila Mouro; Dudas, Rafaela; Zagatto, Mauricio G.r.; Feijoo, Alexander; Brown, George Gardner (Zootaxa, 2023)
Over 150 species of earthworms are known from the Brazilian Atlantic rainforest, but many more are expected to live in this megadiverse biome. In the present study, we evaluated earthworm species occurrence and diversity in native and reforested areas in four National Forests in three Brazilian states: Três Barras National Forest (Santa Catarina), Irati and Piraí do Sul National Forests (Paraná) and Capão Bonito National Forest (São Paulo) using formalin and hand sorting methods. A total of 13 species were found, five exotic and eight natives (of which four were new, undescribed species), belonging to six genera and five families (Rhinodrilidae, Glossoscolecidae, Ocnerodrilidae, Benhamiidae, Megascolecidae). In general, higher number of earthworms were collected in Araucaria plantations, except in Capão Bonito where Pinus sp. plantations had higher abundance. Hand sorting also collected more species in all forests, so this should be the preferred sampling method to evaluate earthworm communities. Formalin extraction was efficient only for epi-endogeic earthworms, most of them exotic species. Exotic pine species plantations tend to reduce species richness and abundance, compared with native forests and Araucaria plantations, and substitution of native vegetation for pine plantations should consider potential negative effects on soil animal populations.